2010
DOI: 10.1258/mi.2010.010041
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and sexual desire: the role of testosterone

Abstract: The present short review underlines the role of testosterone (T) in the motivational and satisfaction components of women's sexuality and critically discusses the strategies to treat hypoactive sexual desire disorder (HSDD), a condition of low desire associated with personal and/or interpersonal difficulties, which is more common in surgical menopausal women. There are multiple ways androgens target the brain regions (hypothalamic, limbic and cortical) involved in sexual function and behaviour. Even though cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 89 publications
0
16
0
2
Order By: Relevance
“…it is well known that the menopausal hypoandrogenism is at the basis of the loss of libido, typical of physiological or surgical menopause, determining a real disease called hypoactive sexual desire disorder (Hsdd), characterized by the lack or absence of sexual fantasies and desire for sexual activity, in combination with marked distress or interpersonal difficulties, very common expecially after ooforectomy (30). in this case it is necessary to correct the androgens and estrogens deficiency, to improve and positively affect the sexual function and mood, but also psycotherapy plays a crucial role when a personal or interpersonal discomfort is evident.…”
Section: Dhea Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…it is well known that the menopausal hypoandrogenism is at the basis of the loss of libido, typical of physiological or surgical menopause, determining a real disease called hypoactive sexual desire disorder (Hsdd), characterized by the lack or absence of sexual fantasies and desire for sexual activity, in combination with marked distress or interpersonal difficulties, very common expecially after ooforectomy (30). in this case it is necessary to correct the androgens and estrogens deficiency, to improve and positively affect the sexual function and mood, but also psycotherapy plays a crucial role when a personal or interpersonal discomfort is evident.…”
Section: Dhea Supplementationmentioning
confidence: 99%
“…in this case it is necessary to correct the androgens and estrogens deficiency, to improve and positively affect the sexual function and mood, but also psycotherapy plays a crucial role when a personal or interpersonal discomfort is evident. A recent study suggests transdermal testosterone at the dose of 300 µg/day as a possible therapy, in combination or not with an estroprogestin treatment, both in physiological and surgical menopause, without any relevant side effects (30).…”
Section: Dhea Supplementationmentioning
confidence: 99%
“…Inne doniesienia również potwierdzają korzystny wpływ na funkcje seksualne kobiet (wzrost pożądania, aktywności i satysfakcji seksualnej zarówno po menopauzie naturalnej, jak i chirurgicznej) stosujących jako uzupełnienie terapii estrogenowej preparatów testosteronu w formie plastrów [23][24][25].…”
Section: Niedobór Androgenów U Kobiet W Okresie Pomenopauzalnymunclassified
“…polepszenie relacji w związku czy leczenie zaburzeń seksualnych partnera. Jej istotnym elementem jest świadoma zgoda pacjentki ze względu na możliwe skutki uboczne terapii [25].…”
Section: Niedobór Androgenów U Kobiet W Okresie Pomenopauzalnymunclassified
“…1 Pertaining to the prevalence of female sexual dysfunction, in the year of 2012, Ambler et al 2 estimated that between 68 and 86.5% of postmenopausal women presented with some kind of sexual problem. In 2010, Nappi et al 3 found that the decrease in female sexual desire is associated with personal and interpersonal difficulties.…”
Section: Introductionmentioning
confidence: 99%